LIFE QUALITY INDICES FOR INFANTS, RESIDING IN THE REPUBLIC OF TATARSTAN - N.L. Rybkina; I.V. Viniarskaya; V.V. Chernikov ("Paediatrician" Publishers LLC, 2007)
The article is devoted to the research of the infants life quality assisted by the qualin questionnaire. It was shown that the quality of life of the healthy children is higher than that of the premature newborns and those from the families of the social risk. The researchers disclosed that the life quality of premature newborns is above all related to the health status and level of the child growth, while the children from the families of the social risk - to the social aspects of life. Key words: infants, quality of life.